PRINCELY HALYCH: ARGUMENTATIVE ISSUES OF THE CITY’S EMERGENCE AND DEVELOPMENT AS THE CAPITAL OF THE LAND-PRINCIPALITY - HOLOVKO, Oleksandr (Halych. Scientific work collection, 2018)
The article is devoted to the stages of formation of Halych as the capital center of the Rostyslavovych dynasty in the late 11–12th centuries. The author emphasizes the continuity of the old tribal Croatian traditions in the region which managed not only to survive after being defeated by the Kyivan(Rus troops at the end of the 10th century, but also to reborn in a new role for themselves. The transit location of Halych and the control of trade flows from north to south and from west to east played an important role for the rapid development of the city. In the 12–13th centuries, Halych was finally located on its current site, divided into the so(called Small (the princely and episcopal residences) and the Great (boyar settlement with the premises of ordinary Galicians). Modern archaeological research makes it possible to «read» the stages of its historical development in this way.